Korean policies on secondary vocational education : efforts to overcome skills mismatch and labor force shortage - Park, Dong-Yeol [Verfasser] (My University, 2011)
"Korea's specialized high schools, which are the main providers of secondary vocational education, significantly contributed to the country's rapid economic development in the past. However, today these schools are facing new challenges to their identity and status as the country's industrial and labor force structures evolve and as demands of parents and students for higher education and elevated status rise. The failure of these schools to adapt to shifting needs of industries and expectations of students have contributed to a labor and skill shortage especially affecting small and medium enterprises (SME). In response to these problems, government, the industries, and institutions of research and education are working together to establish an innovative, demand-oriented and competence-based system of vocational education. This article describes the current trends in the Korean labor market and presents selected policies and initiatives to minimize the existing skills mismatch and labor shortage." (Authors' abstract, BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; S 2.3 Berufsbildungspolitik; I 2.3.4 Asien; Arbeitsmarkt; Mismatch; Fachkräftemangel; Jugendarbeitslosigkeit; Berufsbildungssystem; Reform; Korea